2021
DOI: 10.1148/radiol.2020202568
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chest CT for COVID-19 Pneumonia Diagnosis in France

Abstract: Background The role and performance of chest CT in the diagnosis of the coronavirus disease 2019 (COVID-19) pandemic remains under active investigation. Purpose To evaluate the French national experience using Chest CT for COVID-19, results of chest CT and RT-PCR were compared together and with the final discharge diagnosis used as reference standard. Materials and Methods A structured CT scan survey (NCT04339686) was sent to 26 hospital radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 20 publications
(29 reference statements)
1
66
0
6
Order By: Relevance
“…Radiology has remained at the center of patient' care since the COVID-19 outbreak began. Chest computed tomography (CT) is sensitive at detecting COVID-19 pneumonia though specificities vary between studies, 1 2 and was used in the diagnosis of COVID-19 combined with clinico-epidermiological features in Wuhan where the use of reverse transcription-polymerase chain reaction (RT-PCR) is limited. 3 Chest radiograph is less sensitive than chest CT 4 5 but is useful to access the need for hospitalization in young to middle-aged patients, 6 and to predict progression to critical illness.…”
Section: Introductionmentioning
confidence: 99%
“…Radiology has remained at the center of patient' care since the COVID-19 outbreak began. Chest computed tomography (CT) is sensitive at detecting COVID-19 pneumonia though specificities vary between studies, 1 2 and was used in the diagnosis of COVID-19 combined with clinico-epidermiological features in Wuhan where the use of reverse transcription-polymerase chain reaction (RT-PCR) is limited. 3 Chest radiograph is less sensitive than chest CT 4 5 but is useful to access the need for hospitalization in young to middle-aged patients, 6 and to predict progression to critical illness.…”
Section: Introductionmentioning
confidence: 99%
“…Two are the major clinical impications of our study. First, due to its high sensitivity, CT has been proposed as the primary diagnostic tool in epidemic areas (13,40). Moreover, the WHO recommended chest imaging for the diagnostic workup of symptomatic patients with suspected COVID-19 if RT-PCR testing was unavailable or delayed or when initial RT-PCR testing was negative but patients had high clinical suspicion of COVID-19 (41).…”
Section: Discussionmentioning
confidence: 99%
“…It was my pleasure to read the recently published article "Efficacy of Chest CT for Pneumonia in France" by Herpe and colleagues (1). The authors found no significant difference for sensitivity of chest CT among regions with varying disease prevalence and concluded that chest CT was used successfully in suspicious patients for COVID-19 pneumonia as an initial diagnostic tool.…”
Section: N P R E S Smentioning
confidence: 99%